Spirituality and social support in flood victims - Sipon, Sapora; Sakdan, Mohd Fo'ad; Mustaffa, Che Su; Marzuki, Najib Ahmad; Khalid, Mohamad Sukeri; Ariffin, Mohd Taib; Nik Nazli, Nik Nadian Nisa (Elsevier Ltd., 2015)
Research on flood disasters in the past decade has impacted outcomes such as spirituality and social support. A number of studies have shown that flood also changes the vicitms’ belief about themselves and meaning of life. The purpose of this paper is to explore the relationship between spiritual and social support. The paper is based on a quantitative approach by conducting a survey on 764 flood victims. A questionnaire battery including a translated Malaysian version of spirituality and a Modified version of social support were administered to households in flood affected areas. All analysis were carried out using Statistical Package For The Social Science (SPSS Version 21). The study found that there was significant relationship between spirituality and social support (r = 202**, family, r = 286**,friends, r = 210** and significant others, r = .448**) in flood victims. In sum, this study provide theoretical contributions to spirituality and social support research. The study of the role of spirituality and social support in fostering resilience in flood survivors may advance the understanding of human adaptation and coping to flood trauma.